2006
DOI: 10.1002/jcla.20134
|View full text |Cite
|
Sign up to set email alerts
|

Reference distributions for apolipoproteins AI and B and the apolipoprotein B/AI ratios: a practical and clinically relevant approach in a large cohort

Abstract: The two serum apolipoproteins in the highest concentrations, apolipoprotein (apo) AI and apolipoprotein B, and the apolipoprotein B/AI ratio are measured to assess clinical risk for atherosclerotic heart and peripheral vascular diseases. The study is based on a cohort of over 37,000 Caucasian individuals from northern New England measured in one laboratory by immunonephelometry using standardized reference materials. All samples received for protein analyses were accepted provided adequate identifying informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This is the seventh in a series of meta-analyses for serum protein reference intervals. Our practical approach applied to published population data produces many reference intervals comparable to our companion study (98), which reported reference data for apo AI, apo B, and the B/AI ratio based on over 27,000 observations. Continued.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This is the seventh in a series of meta-analyses for serum protein reference intervals. Our practical approach applied to published population data produces many reference intervals comparable to our companion study (98), which reported reference data for apo AI, apo B, and the B/AI ratio based on over 27,000 observations. Continued.…”
Section: Discussionmentioning
confidence: 90%
“…If a published observation was based on less than 10 observations, it was combined with an adjacent age group from the same publication, if possible, otherwise it was not shown. For purposes of comparison, the solid and dashed lines represent the median levels found for males and females, respectively, in our companion study (98). Figure 1A shows the reported apo AI median values from the 64 published studies considered acceptable.…”
Section: Number Of Studies Available For Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…The mean Apo-A1 levels were significantly reduced in PaCa with respect to HC, patients with ChrPa, DM, and CG and in patients with GC with respect to HC and CG (1-way ANOVA: F = 10.49, P G 0.0001). Because Apo-A1 reference values are dependent on age and sex, Apo-A1 above the 2.5 percentile of the reference values for age and sex were classified as normal, 27 whereas values below this cutoff were classified as low. Low Apo-A1 levels were most frequently found in PaCa (43.2%) and GC (31.3%) cases than in HC (0%), ChrPa (23.1%), CG (0%), and DM (9.8%) (W 2 = 39.87, P G 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…The reference population for the Apo-B/A1 ratio was derived from a large US cohort that included significant numbers within the paediatric age group. 13 A single group mean was used for each element of the lipid profile, as the variation between gender and age groups is minimal with the exception of Apo-A1 and the Apo-B/A1 ratio. 11 Gender-specific means are presented for Apo-A1 and Apo-B/A1 ratio.…”
Section: Definitionsmentioning
confidence: 99%